PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN GUNUNG AGUNG SENAYAN CITY MALL JAKARTA PUSAT - Endang Kustini; Desi Prasetiyani; Muhamad Guruh (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This research aims to determine the effect of compensation (X1) and motivation (X2) together on employee performance (Y), the effect of motivation (X2) on (Y) employee performance and the effect of compensation (X1) on employee performance (Y). The type of research carried out was a quantitative research method by distributing and collecting questionnaires about employee compensation, motivation and performance to 58 respondents. The analysis technique carried out is using Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, Correlation Coefficient Analysis, Determination Coefficient Analysis and Hypothesis Testing. The research results show that providing compensation has a positive and significant effect on employee performance at Gunung Agung Senayan City Mall. This is proven by the value obtained for the regression equation Y = 8.463 + 0.668X1. Hypothesis test results were also obtained for the Compensation variable (X1) on Employee Performance (Y) of 0.000 < 0.05 or a calculated t value of 5.736 > t table 2.003. Motivation has a positive and significant effect on employee performance at Gunung Agung Senayan City Mall). This is proven by the value obtained for the regression equation Y = 9.822 + 0.610X2. Hypothesis test results were also obtained for the Motivation variable (X2) on Employee Performance (Y) of 0.000 < 0.05 or a calculated t value of 5.063 > t table 2.003. And providing compensation and motivation together have a positive and significant effect on employee performance at Gunung Agung Senayan City Mall. This is proven by the value obtained for the regression equation Y = 3.500 + 0.489X1 + 0.389X2, for the influence of the compensation variable (X1) and the motivation variable (X2) on the employee performance variable (Y) is 0.000 < 0.05.